A Fourier transform microspectrometer in a droplet - Malara, Pietro (Il Colle di Galileo, 2021)
An experiment at the National Institute of Optics (INO) of the CNR has shown the possibility of carrying out spectrochemical analysis of a material simply by exploiting the evaporation of a liquid drop on the tip of an optical fiber. Endowed with a proper data analysis procedure, this simple optofluidic system is equivalent to a miniaturized Fourier transform spectrometer, capable of operating automatically and at an extremely low production cost.